Thermal performance of the new superfluid helium vertical test cryostats for magnet tests at CERN. (April 2019) - Vande Craen, A; Bajko, M; Benda, V; Deschamps, J-B; Giloux, C; Lees, A; Parma, V; Pasdeloup, F; Pirotte, O
Abstract: In the frame of the R&D program of the HL-LHC, the upgrade of the Large Hadron Collider (LHC), CERN augmented its test facility with two new large-scale vertical test stations for superconducting magnet testing. The cryostats composing the core of these test stations share design features but are of different dimensions: one allows testing magnets up to 1.5 m diameter, 2.5 m long for a maximum weight of 15 t, while the other can accommodate magnets up to 0.9 m diameter, and 5.5 m long for a maximum weight of 18 t. These test stations are designed to operate at 1.3 bar and at controlled temperatures in the range 1.9 - 4.5 K. They can provide for safe dissipation of stored energy in the magnet coils of up to 10 MJ. After a brief description of the cryostats, this paper describes the qualification measurements of heat loads at 4.5 K and 1.9 K of both cryostats, some design enhancements that were made and the performance improvements obtained.